REDESIGN KURSI BONCENG ANAK YANG ERGONOMIS PADA KENDARAAN RODA DUA - Fia Mega, Ragil Sukma; Zetli, Sri (LPPM Universitas Putera Batam, 2023)
Now it has become a tendency for every parent to bring their baby in all their activities from shopping to malls or traditional markets and not even a few who take their babies while doing work outside the home. many parents wanted a multifunctional pillion chair. One way to do this is to identify what the customer wants and develop pillion chair products using the Quality Function Deployment (QFD) approach. the design concept of the added child pillion chair is to be multifunctional. The multifunctionality in question is that the child's pillion chair has been developed to become a stoller as well so that parents who have children 1-3 years old when traveling using two-wheeled vehicles are not tired of carrying their children. The development of this pillion chair is also based on ergonomic aspects by using the anthropometric method of measuring the child's body. The results of the ergonomic analysis of the child pillion chair using anthropometric calculations are that the seat width is 29cm the seat length is 22cm the backrest height is 31cm the armrest height is 18cm the footrest height is 24cm the seat belt length is 33cm.